Chromaspirina aliapapillata sp.nov. (Nematoda, Desmodorida) from Donuzlav Bay (Crimea, Black Sea) - Revkova, Tatiana N.; Revkov, Nikolai K. (Zootaxa, 2022)
A new species of free-living marine nematode Chromaspirina aliapapillata sp. nov.  from the Donuzlav Bay (Black Sea) is described. Chromaspirina aliapapillata sp. nov.  is characterized by a slender body, buccal cavity with two dorsal teeth, spiral amphids, tail conico-cylindrical and presence of precloacal supplements. The new species differs from other known species of the genus by having two dorsal teeth and presence of 17 to 21 precloacal supplements of which one or two are cup-shaped and rest curved tubes.